Pair formation in relation to climate: Mallard, Eurasian Wigeon and Eurasian Teal wintering in Iceland - Jonsson, J E; Gardarsson, A (Wildfowl, 2001)
The pairing chronologies of Mallard Anas platyrhynchos, Eurasian Wigeon A. penelope and Eurasian Teal A. crecca wintering in Southwest Iceland were studied over the winters of 1997-98 and 1998-99. Mallard paired first of the three species, with over 60% of all females paired by November. Wigeon and Teal had started pairing in early October, and the proportion of paired females increased gradually through winter until spring. In Mallard, the percentage of paired females was 60-70% during midwinter, the last females became paired in March and April. All three species paired later in Iceland than reported in more southern European and North American areas. In all winter months, especially November, December and January, the proportion of paired Mallard females at each location showed a positive relationship with mean monthly temperature. Fewer data are available on other dabbling duck species, but their pairing chronology seems related to climatic conditions.